A pre-feasibility study for a fruit and vegetable canning plant - Quemado Maria Antoinette D.
ABSTRACT A pre-feasibility study was done which covers the following aspects: the Technical Know-How; Marketing Study; Financial Study; and the Managerial Structure. Under the Technical Feasibility, the following were discussed: the historical background and present status of the canning industry; the technical manufacturing of canned fruits and vegetables such as mango juice, peachy papaya, banana sauce, cream style corn, mushroom in brine, green peas and young corn; the characteristics of these products; production schedule and days; the supply and characteristics of the raw materials; rated capacity and equipment balancing; the equipment needed and their prices; location of the plant, building and facilities, plant lay-out; and the computation for electricity and water to be used. Under the Personnel and Technical Know-How, the number of direct and indirect laborers needed as well as their salary were discussed. Under the Marketing Study, sales were also discussed. From the Financial Study the sales plan, manufacturing plan, general and administrative plan, estimated project cost and venture initiation cost were discussed. The initial operating expenses had a total of P 2,779,112.50 or roughly three million. Lastly, the proposed managerial structure was specified for the fruit and vegetable canning pant.